Предмет: Математика,
автор: Btska000
Help me please!!!!
(a*14+ b*14)*2-(a14-b14)*2
Ответы
Автор ответа:
0
(a*14+ b*14)*2-(a14-b14)*2
(a/4 + b/4)*2 - (a/4-b/4)*2
(0.5a + 0.5b) - (0.5a - 0.5b)
0.5a + 0.5b - 0.5a + 0.5b = b
(a/4 + b/4)*2 - (a/4-b/4)*2
(0.5a + 0.5b) - (0.5a - 0.5b)
0.5a + 0.5b - 0.5a + 0.5b = b
Автор ответа:
0
Это немного не то . но всё равно спасибо )
Автор ответа:
0
(a/4+b/4)*2-(a/4-b/4)*2=((a+b)/4)*2-((a-b)/4)*2=(a+b)/2-(a-b)/2=(a+b-a+b)/2=2*b/2=b
Похожие вопросы
Предмет: Другие предметы,
автор: yynyska7
Предмет: Информатика,
автор: KirillStrelkovskiy
Предмет: Литература,
автор: staspavlov2010
Предмет: Литература,
автор: asqwxzsa